Diabetes puts children at-risk for tooth-related disease - Yaacob, Munirah; Ardini, Yunita Dewi; Muhammad Ali, Suhaila; Taib, Mai Nurul Ashikin (Asia Research News, 2020)
A high incidence of tooth-related ‘periodontal’ diseases among a sample of Malaysian children with diabetes suggests these conditions should be given more attention, as is the case with other co-morbidities. Periodontal disease is the sixth most common co-morbidity in people with diabetes. Researchers at the International Islamic University Malaysia (IIUM) examined 64 children, finding a high prevalence (96.8%) of periodontal disease in those with diabetes compared to those without. More than 6% of the children with diabetes who had periodontal disease were found to have untreated or a severe form of periodontal disease.